Anti-inflammatory activity of essential oil of clove (Syzygium aromaticum) in O/W and W/O Creams - Nining Sugihartini; Gina Lestari; Sapto Yuliani (Pharmaciana, 2019)
Previous studies have shown that the formulations of clove bud essential oil (CBEO) with a concentration of 5% in O/W cream and 2.5% in W/O cream have anti-inflammatory properties. The formulations are developed by adding enhancers, namely oleic acid and propylene glycol. The optimum compositions of oleic acid and propylene glycol are 50%:50% in W/O cream and 30%:70% in O/W cream. This study aimed to determine the effects of different compositions of creams on their anti-inflammatory activities. The creams were evaluated for their anti-inflammatory properties using mice with croton oil-induced inflammatory. The mice were sacrificed, and the back skin was removed to make histopathologic preparations at the end of the three-day inflammatory induction to obtain data of epidermal thickness and the number of cells with COX-2 expression. The results showed that the addition of oleic acid and propylene glycol as enhancers increased the anti-inflammatory activity of both O/W and W/O creams. Since the O/W cream decreased the thickness of the epidermis and the number of cells with COX-2 expression more than the W/O cream, the formulation of CBEO in O/W cream is concluded as a better anti-inflammatory than that of W/O cream.Â Â Â